2014
DOI: 10.1073/pnas.1315980111
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of microbial markets

Abstract: Biological market theory has been used successfully to explain cooperative behavior in many animal species. Microbes also engage in cooperative behaviors, both with hosts and other microbes, that can be described in economic terms. However, a market approach is not traditionally used to analyze these interactions. Here, we extend the biological market framework to ask whether this theory is of use to evolutionary biologists studying microbes. We consider six economic strategies used by microbes to optimize the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
139
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 184 publications
(145 citation statements)
references
References 123 publications
1
139
0
Order By: Relevance
“…Researchers have sought to explain such discrepancies, and suggested that spatial heterogeneity of fungal tissues can cause a poor correlation between microscopy and qPCR measurements of fungal colonization (Hart et al 2013). However, using the same fungal strains, positive relationships have been found between fungal gene copy number measured by qPCR and the dry weight of extraradical hyphae (Engelmoer et al 2014, Werner and. Hyphal dry weight, however, can be very laborious to measure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have sought to explain such discrepancies, and suggested that spatial heterogeneity of fungal tissues can cause a poor correlation between microscopy and qPCR measurements of fungal colonization (Hart et al 2013). However, using the same fungal strains, positive relationships have been found between fungal gene copy number measured by qPCR and the dry weight of extraradical hyphae (Engelmoer et al 2014, Werner and. Hyphal dry weight, however, can be very laborious to measure.…”
Section: Discussionmentioning
confidence: 99%
“…Gene copy concentrations of all samples were corrected proportionally to DNA extraction efficiency, and subsequently expressed as target sequence copy number per mg dried root material. Because fungal tissue contains mitochondria, this quantification of mitochondrial target sequences provides speciesspecific information about the amount of fungal tissue (Engelmoer et al 2014, Werner and. R v2.15.3 (2013) was used to perform statistical analyses.…”
Section: Harvestmentioning
confidence: 99%
“…Another idea is that symbiotic N 2 fixation may help alleviate phosphorus limitation because it allows for the secretion of more nitrogen-rich phosphatases, favoring plant phosphorus harvesting (87). Consequentially, high host nutrient demands may increase the benefits of being in a symbiotic relationship (88,89), selecting for persistence of symbiotic capacity. It is still an open question as to whether a high nutrient lifestyle predated symbiosis persistence or the reverse.…”
Section: Discussionmentioning
confidence: 99%
“…Alignment of nucleotide sequences was performed using ClustalW2 (http://www.ebi.ac.uk/Tools/phylogeny/clustalw2_phylogeny/), and sequences showing an identity equal to or higher than 80% were clustered in groups that were highlighted by different background colors. (E. faecium ST17, ST18, ST78 and E. faecalis ST6 and ST16) (7,67,144,203).…”
Section: Enterococcusmentioning
confidence: 99%